2017
DOI: 10.1016/j.ejca.2017.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of the PI3 kinase inhibitor buparlisib (BKM-120) with or without enzalutamide in men with metastatic castration resistant prostate cancer

Abstract: Buparlisib did not demonstrate significant activity in men with mCRPC, suggesting that PI3K inhibition is not sufficient to reverse resistant mCRPC progression. Future studies of PI3K pathway inhibitors with concurrent enzalutamide should develop optimal dosing and focus on selected patients more likely to benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 28 publications
2
50
0
Order By: Relevance
“…Indeed, preclinical models inhibiting both AR and the PI3K/Akt axis show promising results (Carver et al 2011;Toren et al 2015;Yadav et al 2016). However, clinical pilot studies on anti-androgens and PI3K/Akt/mTOR inhibitors show high proportions of severe adverse effects and high rates of treatment discontinuation, with no clear indication that the PI3K/Akt/mTOR inhibitors reached and inhibited their targets in PCa tissues (Armstrong et al 2017;Massard et al 2017;Wei et al 2017). Given the association of increased nuclear mTOR levels with disease evolution, specifically targeting the transcriptional function of mTOR could offer a novel therapeutic avenue for the management of poor-outcome PCa and perhaps other malignancies, with fewer side effects than global PI3K/ Akt/mTOR inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, preclinical models inhibiting both AR and the PI3K/Akt axis show promising results (Carver et al 2011;Toren et al 2015;Yadav et al 2016). However, clinical pilot studies on anti-androgens and PI3K/Akt/mTOR inhibitors show high proportions of severe adverse effects and high rates of treatment discontinuation, with no clear indication that the PI3K/Akt/mTOR inhibitors reached and inhibited their targets in PCa tissues (Armstrong et al 2017;Massard et al 2017;Wei et al 2017). Given the association of increased nuclear mTOR levels with disease evolution, specifically targeting the transcriptional function of mTOR could offer a novel therapeutic avenue for the management of poor-outcome PCa and perhaps other malignancies, with fewer side effects than global PI3K/ Akt/mTOR inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with metastatic renal cell carcinoma progressing on vascular endothelial growth factor (VEGF) targeted therapies, buparlisib (80 mg/day) with bevacizumab (10 mg/kg every 2 weeks), was shown to be a tolerable regimen with preliminary activity [116]. In patients with castration-resistant prostate cancer, buparlisib did not demonstrate significant activity in a phase II trial, furthermore, the combination of buparlisib with abiraterone acetate was not recommended as a phase Ib study reported [86,117].…”
Section: Pf-04691502 and Pf-05212384 (Gedatolisib Pki-587)mentioning
confidence: 99%
“…Yet, the drug response profiles clearly distinguished the two patients. For the uterine carcinosarcoma case, they identified the combination of the PIK3 inhibitor buparlisib (Armstrong et al , ) with the hypoxia signalling suppressor vorinostat (Zhang et al , ) as one of the top drug combinations. By contrast, for the endometrial adenocarcinoma case, a combination of buparlisib with the PARP and HDAC inhibitor olaparib (Yuan et al , ) was found as optimal treatment in both PDTO and PDTX models.…”
Section: Drug Screens and Personalized Medicine Using Pdtx And Pdto Mmentioning
confidence: 99%